Quadros médicos: Egas Moniz, por José Malhoa - Oliveira, Victor (2014)
Copyright © Ordem dos Médicos 2014. Acta Médica Portuguesa is licensed under a Creative Commons Attribution Non-Commercial License (CC BY NC).